Juggling flaming chain saws : academics in educational leadership try to balance work and family - Marshall, Joanne M. (Work-life balance., 2012)
Challenges of work-life balance in the academy stem from policies and practices which remain from the time when higher education was populated mostly by married White male faculty. Those faculty were successful in their academic work because they depended upon the support of their wives to manage many of the not-work aspects of their lives. Imagine a tweedy middle-aged white man, coming home from the university to greet his wife and children and eat the dinner she's prepared for him, and then disappearing into his study for the rest of the evening with his pipe to write and think great thoughts. If that professor ever existed, he is now emeritus.Juggling Flaming Chainsaws is the first book in a new series on these challenges of managing academic work and not-work. It uses the methodology of autoethnography to introduce the work-life issues faced by scholars in educational leadership. While the experiences of scholars in this volume are echoed across other fields in higher education, educational leadership is unique because of its emphasis on preparing people for leadership roles within higher education and for preK-12 schools. Authors include people at different places on their career and life course trajectory, people who are partnered and single, gay and straight, with children and without, caring for elders, and managing illness. They hail from different geographic areas of the nation, different ethnic backgrounds, and different types of institutions. What all have in common is commitment to engaging with this topic, to reflecting deeply upon their own experience, and to sharing that experience with the rest of us.